2023
DOI: 10.18632/aging.204712
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic significance and immune correlation of SLC10A3 in low-grade gliomas revealed by bioinformatic analysis and multiple immunohistochemistry

Abstract: Purpose: Despite the fact that genetic risk factors contribute to low-grade gliomas (LGGs), the role of critical genes as prognostic and theraputic biomarkers is quite limited. This study is designed to comprehensively investigate the prognostic role and predictive ability of solute carrier family 10 member 3 ( SLC10A3 ) for immunotherapy in LGGs. Methods: We analyzed the prognostic value of SLC10A3 from multiple datasets of LGG patients, and explored it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Specifically, SLC10A3 plays a critical role in regulating the immune response in liver cancer, related with stromal CD4 T cells, CD20 B cells, and macrophage [ 9 ]. Upregulation of SLC10A3 mRNA is statistically related with unfavorable survival outcomes and immune infiltration among low-grade gliomas [ 21 ]. Nonetheless, there is currently no literature on SLC10A3 in colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, SLC10A3 plays a critical role in regulating the immune response in liver cancer, related with stromal CD4 T cells, CD20 B cells, and macrophage [ 9 ]. Upregulation of SLC10A3 mRNA is statistically related with unfavorable survival outcomes and immune infiltration among low-grade gliomas [ 21 ]. Nonetheless, there is currently no literature on SLC10A3 in colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In liver cancer, high DXS253E protein levels were observed to be significantly associated with immune cell infiltration and poor prognosis [ 22 ]. In terms of LGG, higher DXS253E expression levels contribute to programmed cell death and immune infiltration, resulting in poor prognosis of the patients with LGG [ 40 ]. Consistently, Ma et al also found that the upregulation of DXS253E is associated with poor OS in LGG and glioblastoma [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tian et al confirmed significant associations between DXS253E expression and CD4 + Tconv and tumor-infiltrating CD20 + B cells via bioinformatics analysis and multispectral imaging techniques in HCC [ 22 ]. Similarly, a LGG study showed that DXS253E expression was associated with macrophage, CD4 + Tconv cell, and B cell levels [ 40 ]. We consistently found that DXS253E levels were associated with the level of multiple immune-related genes and immune cell infiltration in CRC.…”
Section: Discussionmentioning
confidence: 99%